2019
DOI: 10.1111/tid.13175
|View full text |Cite
|
Sign up to set email alerts
|

Penicillin allergy skin testing as an antibiotic stewardship intervention reduces alternative antibiotic exposures in hematopoietic stem cell transplant recipients

Abstract: Background: Antibiotic allergy de-labeling using penicillin allergy skin testing (PAST) can reduce the use and cost of alternative, non-β-lactam antibiotics in general inpatient populations. This strategy's role in hematopoietic stem cell transplant (HSCT) recipients is unclear. Methods: This study aimed to determine the effect of a pre-transplant PAST protocol on antibiotic use, days of therapy (DOT), and cost in an immunocompromised population at a single center from 7/1/2010-2/1/2019. Patients who received … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 28 publications
0
14
0
3
Order By: Relevance
“…12 Modi et al reported 13% prevalence of BLA label among an American cohort of hematopoietic stem cell transplant (HSCT) candidates. 13 Another study investigated overall reports of antibiotic allergy with 29% of a combined transplant cohort (35% HSCT and 65% SOT) reporting an antibiotic allergy; 16% reported BLA, while 12%, 8.5%, and 5% reported penicillin, TMP-SMX antibiotic, and cephalosporin allergy label, respectively. 4 McLaughlin et al reported a similar rate of TMP-SMX allergy labels with 9.7% of American kidney transplant cohort acquiring this new allergy after being placed on TMP-SMX for Pneumocystis jirevicii pneumonia prophylaxis 14 ; however, Urbancic et al found higher prevalence of reported TMP-SMX allergy label in an Australian kidney transplant cohort with 35% reporting this allergy.…”
Section: Prevalencementioning
confidence: 99%
See 2 more Smart Citations
“…12 Modi et al reported 13% prevalence of BLA label among an American cohort of hematopoietic stem cell transplant (HSCT) candidates. 13 Another study investigated overall reports of antibiotic allergy with 29% of a combined transplant cohort (35% HSCT and 65% SOT) reporting an antibiotic allergy; 16% reported BLA, while 12%, 8.5%, and 5% reported penicillin, TMP-SMX antibiotic, and cephalosporin allergy label, respectively. 4 McLaughlin et al reported a similar rate of TMP-SMX allergy labels with 9.7% of American kidney transplant cohort acquiring this new allergy after being placed on TMP-SMX for Pneumocystis jirevicii pneumonia prophylaxis 14 ; however, Urbancic et al found higher prevalence of reported TMP-SMX allergy label in an Australian kidney transplant cohort with 35% reporting this allergy.…”
Section: Prevalencementioning
confidence: 99%
“…Modi et al. reported 13% prevalence of BLA label among an American cohort of hematopoietic stem cell transplant (HSCT) candidates 13 . Another study investigated overall reports of antibiotic allergy with 29% of a combined transplant cohort (35% HSCT and 65% SOT) reporting an antibiotic allergy; 16% reported BLA, while 12%, 8.5%, and 5% reported penicillin, TMP‐SMX antibiotic, and cephalosporin allergy label, respectively 4 .…”
Section: Prevalencementioning
confidence: 99%
See 1 more Smart Citation
“…Finally, Modi et al 48 performed a retrospective chart review examining the use of non–β-lactam alternative antibiotics during pre-implementation and post-implementation of PST in HCT recipients. 48 Of 1560 patients who underwent inpatient autologous or allogenic HCT, 208 (13.3%) reported a β-lactam allergy. During the post-implementation period, 54% with allergies underwent PST, and no adverse events were observed.…”
Section: Allergy Assessmentsmentioning
confidence: 99%
“…In addition to a robust body of literature supporting the safety and efficacy of penicillin skin testing and direct challenges among immunocompetent hosts [ 5 , 19–22 ], BLA evaluation and de-labeling interventions targeting surgical patient populations have been demonstrated to be associated with increased use of first-line perioperative antibiotics [ 23–25 ]. Furthermore, data regarding the safe use of penicillin skin testing among immunocompromised hosts and transplant candidates have begun to accumulate in recent years [ 26–29 ]. As a result, considering the high proportion of SOT recipients with a BLA and the certainty that their posttransplant course will involve antibiotic exposures, pretransplant evaluation of BLAs should be a priority for this population.…”
Section: Discussionmentioning
confidence: 99%